2013
DOI: 10.1111/jscm.12013
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐Analysis of Supply Chain Integration and Firm Performance

Abstract: As supply chain activities become more dispersed among customers, suppliers and service providers, there is an increased need for customers and suppliers to work together more closely. Supply chain integration (SCI) has been a highly researched topic during the last 20 years. A metaanalytic approach is used to provide a quantitative review of the empirical literature in SCI, and examines relevant design and contextual factors. Eighty independent samples across 86 peer-reviewed journal articles, yielding a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
456
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(543 citation statements)
references
References 162 publications
29
456
1
4
Order By: Relevance
“…There is precedent for this absence of synergy (Sueyoshi & Goto, 2011), performed in an industry in which firms have a significant concentration of fixed assets is significant within the balance sheet (Troy (Almanac of Business and Industrial Financial Ratios), 2008; Troy (Almanac of Business & Industrial Financial Ratios), 2014), which is comparatively with the brewing industry. Additionally, as an alternative methodology, there is precedent in these conclusions with meta-analysis, where results also show lesser relationships, in which immediate benefits have no significant interaction between financial and operational performance (Leuschner, Rogers & Charvet, 2013). This matches with the premise that operational integration and increased performance may be bound by different business constraints (Christopher & Holweg, 2011), which is not essentially driven in the same perspective as the appreciation of financial performance as a measurement of a firms' results (Germain, Davis-Sramek, Lonial & Raju, 2011).…”
Section: Results Analysismentioning
confidence: 54%
“…There is precedent for this absence of synergy (Sueyoshi & Goto, 2011), performed in an industry in which firms have a significant concentration of fixed assets is significant within the balance sheet (Troy (Almanac of Business and Industrial Financial Ratios), 2008; Troy (Almanac of Business & Industrial Financial Ratios), 2014), which is comparatively with the brewing industry. Additionally, as an alternative methodology, there is precedent in these conclusions with meta-analysis, where results also show lesser relationships, in which immediate benefits have no significant interaction between financial and operational performance (Leuschner, Rogers & Charvet, 2013). This matches with the premise that operational integration and increased performance may be bound by different business constraints (Christopher & Holweg, 2011), which is not essentially driven in the same perspective as the appreciation of financial performance as a measurement of a firms' results (Germain, Davis-Sramek, Lonial & Raju, 2011).…”
Section: Results Analysismentioning
confidence: 54%
“…Since most prior research merely examines the direct effects of supply chain integration tactics on performance, without considering the interrelationships between these integration tactics, the reported results are often unclear (e.g. Rai et al, 2006;Leuschner et al, 2013;Mackelprang et al, 2014). Leuschner et al (2013), for instance, found no significant relationship between operational integration and performance.…”
Section: Linking Information Exchange and Operational Integrationmentioning
confidence: 99%
“…Leuschner et al (2013), for example, analyze the impact of individual integration tactics, such as information integration and operational integration, on performance, but do not consider interrelationships among these integration tactics. Zhou and Benton (2007) do consider these interrelationships, but they do not take them into account when relating them to operational performance.…”
Section: Introductionmentioning
confidence: 99%
“…This has invoked numerous questions on the concept (see for e.g., Fabbe-Costes & Jahre, 2006;Fabbe-Costes & Jahre, 2008;Vaart & Donk, 2008;Flynn et al, 2010;Leuschner et al, 2012) and it is believed that the incomplete definition of the concept has partly accounted for the inconsistencies in previous research findings (Flynn et al, 2010).…”
Section: Supply Chain Integration (Sci)mentioning
confidence: 58%